Effect of substrate temperature on magnetic properties of MnFe2O4 thin films - Prabhu Rajagiri (AIP Advances, 2018)
MnFe2O4 thin films were pulsed laser deposited on to quartz substrate from room temperature (RT) to 650 °C in a pure argon environment. Temperature dependence of spontaneous magnetization (4πMS) was measured on these films from 10 K to 350 K using a vibrating sample magnetometer. Ferromagnetic resonance (FMR) study was also carried out at 300 K. The exchange stiffness constant (D) values were obtained by fitting the 4πMS data to the Bloch’s equation. The D values of the films thus found decreases while the 4πMS value increases, though non-monotonically, with the increase in TS and tend to reach bulk values at TS = 650 °C. The variation in D and 4πMS values of the films are explained based on the degree of inversion and oxidation state of cations in thin films.